Cuidado de menores afectados por cáncer u otra enfermedad grave - Sánchez Trigueros, Carmen (Revista de Derecho, 2019)
The 21st disposal. two of the Law 39/2010 of 22 December, the General State Budget for 2011 (BOE of 23 December), introduced in Part II of the General Law of Social Security a new Chapter IV regulates a novel e provide our Social Security system called “provision for the care of children affected by cancer or other serious disease. “ This new provision would involve a legislative change, specifically the General Law of Social Security (LGSS), the Statute of Workers and the Civil Service Basic Statute.